Study of the Features of Readiness for School Education of Preschool Children with Mental Retardation - Marfenko O. V. (Interactive science, 2020)
the article describes a diagnostic study of readiness for school in children with mental retardation by the method of N. Y. Semago, M. M. Semago.
Keywords: задержка психического развития; дошкольный возраст; готовность к школьному обучению; preschool age; mental retardation; school readiness